Metal recovery from spent lithium-ion batteries via two-step bioleaching using adapted chemolithotrophs from an acidic mine pit lake - Lalropuia, Lalropuia; Kucera, Jiri; Rassy, Wadih Y.; Pakostova, Eva; Schild, Dominik; Mandl, Martin; Kremser, Klemens; Guebitz, Georg M. (Frontiers in Microbiology, 2024)
The demand for lithium-ion batteries (LIBs) has dramatically increased in recent years due to their application in various electronic devices and electric vehicles (EVs). Great amount of LIB waste is generated, most of which ends up in landfills. LIB wastes contain substantial amounts of critical metals (such as Li, Co, Ni, Mn, and Cu) and can therefore serve as valuable secondary sources of these metals. Metal recovery from the black mass (shredded spent LIBs) can be achieved via bioleaching, a microbiology-based technology that is considered to be environmentally friendly, due to its lower costs and energy consumption compared to conventional pyrometallurgy or hydrometallurgy. However, the growth and metabolism of bioleaching microorganisms can be inhibited by dissolved metals. In this study, the indigenous acidophilic chemolithotrophs in a sediment from a highly acidic and metalcontaminated mine pit lake were enriched in a selective medium containing iron, sulfur, or both electron donors. The enriched culture with the highest growth and oxidation rate and the lowest microbial diversity (dominated by Acidithiobacillus and Alicyclobacillus spp. utilizing both electron donors) was then gradually adapted to increasing concentrations of Li + , Co 2+ , Ni 2+ , Mn 2+ , and Cu 2+ . Finally, up to 100% recovery rates of Li, Co, Ni, Mn, and Al were achieved via two-step bioleaching using the adapted culture, resulting in more effective metal extraction compared to bioleaching with a non-adapted culture and abiotic control.